2018
DOI: 10.1002/anie.201808554
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spirocyclic Ethers by Enantioselective Copper‐Catalyzed Carboetherification of Alkenols

Abstract: Spirocyclic ethers can be found in bioactive compounds. This copper-catalyzed enantioselective alkene carboetherification provides 5,5-, 5,6- and 6,6-spirocyclic products containing fully substituted chiral carbon centers with up to 99 % enantiomeric excess. This reaction features the formation of two rings from acyclic substrates, 1,1-disubstituted alkenols functionalized with either arenes, alkenes, or alkynes, and clearly constitutes a powerful way to synthesize chiral spirocyclic ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Asymmetric carbooxygenative difunctionalization of C-C double bonds is an efficient reaction that simultaneously incorporates two functionalities and can quickly build complex molecules from bulk chemicals [34][35][36][37][38][39][40][41][42][43][44][45][46] . In the category of radical asymmetric transformations, Buchwald et al developed a two-component asymmetric oxyfunctionalization of alkenes with intramolecular carboxylic acid groups 36,37,40 , and Liu et al reported enantioselective oxyfunctionalization of alkenes with linked alcohols and oximes 39,41,44,45 .…”
mentioning
confidence: 99%
“…Asymmetric carbooxygenative difunctionalization of C-C double bonds is an efficient reaction that simultaneously incorporates two functionalities and can quickly build complex molecules from bulk chemicals [34][35][36][37][38][39][40][41][42][43][44][45][46] . In the category of radical asymmetric transformations, Buchwald et al developed a two-component asymmetric oxyfunctionalization of alkenes with intramolecular carboxylic acid groups 36,37,40 , and Liu et al reported enantioselective oxyfunctionalization of alkenes with linked alcohols and oximes 39,41,44,45 .…”
mentioning
confidence: 99%
“…The enantiomeric purity of product 2 a was improved to 99% ee through a simple recrystallizatin in i-PrOH. Further, several different types of N,N-ligands L2-L5 were also explored and all the results were inferior to that of L1 (Table 1, entries [6][7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…[6,7] However, the highly enantioselective synthesis of chiral spirocyclic compounds still remains as a great challenge since asymmetric induction at the rigid spiro carboncenter always requires a very active catalytic system. [8] For our interests to develop asymmetric methods for the construction of chiral spirocyclic compounds, we have developed a copper-catalysed double Narylation reaction for the formation of spirobilactams. [9] To continue the research in this field, herein we'd like to report our work in the asymmetric synthesis of oxa-spirocycles through copper-catalysed double O-arylation (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This report was the first example of metal-catalyzed enantioselective cyclohydroalkoxylation of unactivated alkenes. Last year, inspired by their previous works on copper(II)-catalyzed enantioselective carboetherifications of alkenols [118][119][120][121], the group of Chemler reported the enantioselective cyclohydroalkoxylation of a range of aliphatic 4-and 5-alkenols catalyzed by chiral copper(II) bis(oxazoline) (Figure 22 [122]. In the presence of an oxidant and an H-atom donor, the Cu(OTf) 2 /(S,S)-i-Pr-Box (L 7 ) or (S,S)-Ph-Box (L 8 ) system is indeed an efficient system to access enantioenriched α-chiral substituted tetrahydrofurans, phthalans, isochromans and morpholine from primary and tertiary alcohols tethered to the terminal, 1,1-and 1,2-disubstituted alkenes as illustrated in Figure 22.…”
Section: Hydroalkoxylationmentioning
confidence: 99%